2017
DOI: 10.1371/journal.pone.0172546
|View full text |Cite
|
Sign up to set email alerts
|

The origin and biogeographic diversification of fishes in the family Poeciliidae

Abstract: The fish subfamily Poeciliinae (sensu Parenti, 1981) is widely distributed across the Western Hemisphere and a dominant component of the fish communities of Central America. Poeciliids have figured prominently in previous studies on the roles of dispersal and vicariance in shaping current geographic distributions. Most recently, Hrbek et al. combined a DNA-based phylogeny of the family with geological models to provide a biogeographic perspective that emphasized the role of both vicariance and dispersal. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(153 citation statements)
references
References 70 publications
(163 reference statements)
12
138
1
2
Order By: Relevance
“…lamp-eye clade as supported by morphological studies (Roberts 1970, Parenti 1981, Costa 1996, Ghedotti 2000. Although the position of F. simplex is only moderately supported in the analyses, other studies using different molecular data sets indicate that Fluviphylax is not closely related to African lamp-eyes (Pollux et al 2014;Reznick et al 2017). …”
Section: Phylogenetic Position Of Pantanodon and African Lamp-eyesmentioning
confidence: 53%
See 2 more Smart Citations
“…lamp-eye clade as supported by morphological studies (Roberts 1970, Parenti 1981, Costa 1996, Ghedotti 2000. Although the position of F. simplex is only moderately supported in the analyses, other studies using different molecular data sets indicate that Fluviphylax is not closely related to African lamp-eyes (Pollux et al 2014;Reznick et al 2017). …”
Section: Phylogenetic Position Of Pantanodon and African Lamp-eyesmentioning
confidence: 53%
“…These studies indicated the African Procatopodinae as the sister group of a clade comprising European non-Poeciliidae cyprinodontoid genera (Valencia Myers, 1928 andAphanius Nardo, 1827). In addition, Pollux et al (2014) and Reznick et al (2017) based on a broad sample of New World cyprinodontoid taxa supported the South American Fluviphylax as the sister group of a Neotropical clade comprising Poeciliinae and Anablepidae, but did not include Pantanodon in their analyses. A species of the latter genus, Pantanodon stuhlmanni (Ahl, 1924) was tentatively included in a phylogenetic analysis (Pohl et al 2015), based on two mitochondrial and three nuclear genes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…() and Reznick et al. (). This low uncertainty in the phylogenetic relationships among the subgenera of Poecilia indicates that results of comparative analyses using either tree should be identical (Hernandez et al.…”
Section: Resultsmentioning
confidence: 99%
“…) and are two of the most speciose clades in the family (Reznick et al. ), which indicates that phenotypic evolution of enlarged dorsal or caudal fins may have led to rapid speciation in these livebearers.…”
Section: Discussionmentioning
confidence: 99%